A review of Apha floralis species group (Lepidoptera: Eupterotidae) - Zolotuhin, Vadim V.; Pugaev, Sergey N.; Du, Tran Thieu (Acta Biologica Sibirica, 2020)
5 species of the genus Apha Walker, 1855 are included here under the floralis group, three of which are described as new: A. zephyrus sp. nov. (type locality: China, Yunnan, Dianceng Shan, 2.200 m), A. witti sp. nov. (type locality: China, Sichuan, Qionglai Shan, 1.400 m) and A. chloralis sp. nov. (type locality: Vietnam, Cha Val, Nam Giang, Quang Nam, 546 m). Types of all species are illustrated, biology and morphology of preimaginal instars are discussed for A. kantonensis Mell, [1930] and A. chloralis sp. nov. A new synonymy for Apha Walker, 1855 and Preptothauma Draudt, 1931 (including a single mislabeled species P. oxydiata Draudt, 1931), syn. nov. is established.